2011
DOI: 10.1088/0031-9155/56/6/003
|View full text |Cite
|
Sign up to set email alerts
|

Improved total variation-based CT image reconstruction applied to clinical data

Abstract: In computed tomography there are different situations where reconstruction has to be performed with limited raw data. In the past few years it has been shown that algorithms which are based on compressed sensing theory are able to handle incomplete datasets quite well. As a cost function these algorithms use the ℓ(1)-norm of the image after it has been transformed by a sparsifying transformation. This yields to an inequality-constrained convex optimization problem. Due to the large size of the optimization pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
204
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 277 publications
(204 citation statements)
references
References 19 publications
0
204
0
Order By: Relevance
“…In these cases, the rotate-plus-shift trajectory may be combined with reconstruction algorithms dedicated to avoid limited angle artifacts. 6,8 The proposed trajectory allows for the acquisition of a fully sampled data set with a mobile C-arm system mechanically limited to a rotation range of at least 180…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these cases, the rotate-plus-shift trajectory may be combined with reconstruction algorithms dedicated to avoid limited angle artifacts. 6,8 The proposed trajectory allows for the acquisition of a fully sampled data set with a mobile C-arm system mechanically limited to a rotation range of at least 180…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] These techniques, however, do not achieve image quality or size of the reconstructed volume comparable to the short scan reference.…”
Section: Introductionmentioning
confidence: 99%
“…The minimization technique is used to bring down the number of missing coefficients. They discussed two models of Alternating Minimization algorithm such that one model follows the sparsity and other one follows Total Variation [77]. This algorithm is applied for MRI reconstruction which was then a comparatively latest imaging technology that is capable of resolving the image using spatial and temporal atomic scale.…”
Section: A Alternating Minimizationmentioning
confidence: 99%
“…First, we investigate the iTV approach [6], where the regularization term is the total variation norm R TV (x) = x TV . In this case operator T is given by an iterative gradient descent procedure with automatic adaption of the TV gradient step size to assure improved data consistency after one iteration of Algorithm 1.…”
Section: End Formentioning
confidence: 99%
“…For the rapid scanning protocol we recently applied an iterative tight frame (TF) wavelet-based reconstruction algorithm [3] in a brain perfusion phantom study [4] to increase CNR in the tissue TACs, which showed promising results to improve the perfusion maps compared to FDK [5] reconstruction. In this work, we compare the latter approach to the JBF and the improved total variation (iTV) [6] regularization techniques. However, all these approaches are based on ART [7] and thus computationally expensive.…”
Section: Introductionmentioning
confidence: 99%